2003
DOI: 10.1002/cncr.11251
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient, sequential, parenteral‐oral antibiotic therapy for lower risk febrile neutropenia in children with malignant disease

Abstract: BACKGROUNDRecent reports and previous randomized trials conducted at the authors' institution suggested that children with lower risk febrile neutropenic (LRFN) may benefit from substitution of oral antibiotic therapy for parenteral therapy. The objective of this study was to determine the efficacy of parenteral‐oral outpatient therapy in the management of children with LRFN who were receiving treatment for malignant disease.METHODSFrom August 2000 to April 2002, 135 children with a median age of 7.5 years (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 29 publications
(67 reference statements)
2
30
0
14
Order By: Relevance
“…The finding that the experimental treatment was non-inferior to continued standard treatment regarding efficacy is in line with results of published RCT on first-day step-down to oral antimicrobial therapy in pediatric low-risk FN, though with different definitions of efficacy [12][13][14][15]. These studies had found no significant difference of efficacy between oral and intravenous antimicrobial therapy, always applied in outpatient settings.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The finding that the experimental treatment was non-inferior to continued standard treatment regarding efficacy is in line with results of published RCT on first-day step-down to oral antimicrobial therapy in pediatric low-risk FN, though with different definitions of efficacy [12][13][14][15]. These studies had found no significant difference of efficacy between oral and intravenous antimicrobial therapy, always applied in outpatient settings.…”
Section: Discussionsupporting
confidence: 78%
“…The non-inferiority [20,26,27] tests used here led to more stringent results than the difference tests used in the comparable RCT published [12][13][14][15] and in a recent meta-analysis [16]. This led to positive evidence here that the experimental treatment was non-inferior to the standard treatment regarding efficacy.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations